A tight lower bound for restricted pir protocols - Beigel, Richard; Fortnow, Lance; Gasarch, William (Computational complexity, 2006)
We show that any 1-round 2-server Private Information Retrieval Protocol where the answers are one bit long must ask questions that are at least n−2 bits long, which is nearly equal to the known n−1 upper bound. This improves upon the approximately 0.25n lower bound of Kerenidis and deWolf while avoiding their use of quantum techniques.